Mobile intelligent autonomous systems - Raol, J. R. 1947-; Gopal, Ajith K. (Taylor & Francis, 2013)
"Written for systems, mechanical, aero, electrical, civil, industrial, and robotics engineers, this book covers robotics from a theoretical and systems point of view, with an emphasis on the sensor modeling and data analysis aspects. With the novel infusion of NN-FL-GA paradigms for MIAS, this reference blends modeling, sensors, control, estimation, optimization, signal processing, and heuristic methods in MIAS/robotics, and includes examples and applications throughout. The organization of the book is based on fundamental concepts, with sections covering fundamental concepts, methods and approaches, block/flow diagrams, and numerical examples. A MATLAB-based approach is used through selected case studies in the text"- Resumé vydavatel
Keywords: motorová vozidla; mobilní roboty; automatické řízení; řídicí systémy; motor vehicles; mobile robots; automatic control; control systems; inteligentní kontrolní systémy; sborníky; elektronické knihy; papers of several authors; electronic books